Psychologiczne uwarunkowania decyzji zakupu samochodów luksusowych - Klimkowska, Regina (Wydawnictwo Uniwersytetu Rzeszowskiego, 2009)
Autorka w swym artykule koncentruje się na przedstawieniu rynku samochodów luksusowych. Rynek samochodów luksusowych jest segmentem rynku nowych samochodów osobowych w Polsce. Możemy zobaczyć znaczący spadek sprzedaży nowych samochodów od roku 1999 aż do dzisiaj. W 1999 r. sprzedano ok. 640 000 nowych aut, a w 2007 r. tylko 293 300. Całkiem nowym zjawiskiem jest rynek nowych samochodów luksusowych. Sprzedaż na rynku nowych samochodów luksusowych systematycznie wzrastała. W 2000 r. wynosiła 4800 aut, w 2007 r. sprzedano już ok. 16 000 luksusowych aut. Artykuł prezentuje najważniejsze czynniki psychologiczne determinujące ten rynek.

This article is focused on the description of the luxury cars market. The luxury cars market is a segment of the Polish total new cars market. We can see the significant decline in the new cars market from 1999 till now. In year 1999 the amount of the new sold cars was about 640 000 cars but in the year 2007 only 293 300 new cars were sold. There is quite a different phenomena in the new luxury cars market in Poland. The total amount of the sold new luxury car was steadily growing up from 4800 in the year 2000 up to 16 000 in the year 2007. The author describes the main psychological factors determining this market.
Psychological Determinants of Buying Decisions in the Polish Luxury Cars Market